The British Trade-Union Congress of 1902 - Durand, E. Dana (Quarterly Journal of Economics, 1902)
The British Trade-Union Congress of 1902 E. Dana Durand E. Dana Durand Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 17, Issue 1, November 1902, Pages 181–184, https://doi.org/10.2307/1884715 Published: 01 November 1902